2014
DOI: 10.1021/es502244v
|View full text |Cite
|
Sign up to set email alerts
|

Using Discriminant Analysis to Determine Sources of Salinity in Shallow Groundwater Prior to Hydraulic Fracturing

Abstract: High-volume hydraulic fracturing (HVHF) gas-drilling operations in the Marcellus Play have raised environmental concerns, including the risk of groundwater contamination. Fingerprinting water impacted by gas-drilling operations is not trivial given other potential sources of contamination. We present a multivariate statistical modeling framework for developing a quantitative, geochemical fingerprinting tool to distinguish sources of high salinity in shallow groundwater. The model was developed using new geoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…While groundwater from the current study in New York State resembles previous results documented in Pennsylvania, West Virginia, and New York (Heisig and Scott ; Darrah et al , ; Lautz et al ; Harkness et al ), the magnitude of chemical variation is much higher in Pennsylvania groundwater than that in New York. For example, the highest concentrations of helium documented in New York are 37,090 × 10 −6 ccSTP/L, which is nearly an order of magnitude lower than Pennsylvania (403,035 × 10 −6 ccSTP/L) (Darrah et al , ).…”
Section: Discussionsupporting
confidence: 78%
“…While groundwater from the current study in New York State resembles previous results documented in Pennsylvania, West Virginia, and New York (Heisig and Scott ; Darrah et al , ; Lautz et al ; Harkness et al ), the magnitude of chemical variation is much higher in Pennsylvania groundwater than that in New York. For example, the highest concentrations of helium documented in New York are 37,090 × 10 −6 ccSTP/L, which is nearly an order of magnitude lower than Pennsylvania (403,035 × 10 −6 ccSTP/L) (Darrah et al , ).…”
Section: Discussionsupporting
confidence: 78%
“…In this case, we would expect coincidence of Na‐rich waters that reflect mixing of fresh and saline water and elevated thermogenic methane concentrations. Other prior studies have also found strong associations between basin brine mixing with shallow groundwater and occurrence of methane [ Lautz et al ., ; Warner et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous applications of inorganic and isotopic tracers of dissolved salts and hydrocarbon and noble gas geochemical tracers have revealed the influence of the tectonic and hydrogeological setting on water quality and natural contamination in areas of oil and gas development both in the NAB and elsewhere (Darrah et al, 2015b;Engle and Rowan, 2014;Llewellyn, 2014, Lautz et al, 2014Molofsky et al, 2013;Mortiz, 2015;Revesz et al, 2010;Schon, 2011;Sharma and Baggett, 2011;Siegel et al, 2015a;Siegel et al, 2015b;Warner et al, 2012, Warner et al, 2013b, Wunsch, 1992.…”
mentioning
confidence: 99%